혼합 샘플링을 이용한 하이브리드 딥러닝 결합 모델 기반의 부정맥 분류 - 조익성(Ik-Sung Cho); 권혁숭(Hyeog-Soong Kwon) (한국정보통신학회논문지, 2024)
부정맥은 심장 박동이 불규칙하게 뛰고 있는 상태를 말하며, 심정지와 같은 위험한 상황을 유발할 수 있기 때문에 이의 조기 검출은 매우 중요하다. 본 연구에서는 혼합 샘플링 기법과 어텐션 메커니즘 기반의 하이브리드 딥러닝 결합 모델을 이용한 부정맥 분류 방법을 제안한다. 이를 위해 먼저 전처리 과정을 거친 심전도 신호를 사용하였다. 이때 데이터의 불균형 문제를 해결하기 위해 SMOTE-Tomek 혼합 샘플링 기법을 적용하였다. 이후 컨볼루션 레이어를 통해 부정맥 신호의 패턴을 추출하고 이를 BLSTM 레이어에 입력한 후 어텐션 메커니즘을 통해 가중치를 학습하고 검증 데이터로 모델을 평가한 후 부정맥을 분류하였다. 제안한 방법의 타당성을 판단하기 위해 MIT-BIH 부정맥 데이터베이스를 통해 분류의 정확도, 정밀도, 재현율, F1-score를 비교하였다. 성능평가 결과 각각 99.64%, 93.27%, 95.05%, 94.08%로 분류율이 우수함을 확인할 수 있었다. Arrhythmia is an irregular heartbeat, and its early detection is very important because it can cause dangerous situations such as sudden cardiac death. In this study, we propose a method for arrhythmia classification using a hybrid deep learning combination model based on mixed sampling technique and attention mechanism. To do this, we used preprocessed ECG signals. The SMOTE-Tomek mixed sampling technique was applied to address the imbalance in the data. The convolutional hierarchy was then configured to precisely extract the pattern of the arrhythmia signal, which was used as the input of BLSTM, and then the weights were learned through an attention mechanism, and the model was evaluated with validation data to verify the change in normal and arrhythmia classification. To demonstrate the superiority of the proposed method, we compared the accuracy, precision, recall, and F1-score of the classification using the MIT-BIH arrhythmia database. The performance evaluation results showed that the classification rates were 99.64%, 93.27%, 95.05%, and 94.08%, respectively. KCI Citation Count: 0